(untitled) - Currtis, Graham (Harlow, England, 2004)
"Well written and stimulating reading." ndash; Thomas W. De Boer, University of Groningen Business Information Systems 5 th edition offers today's BIS students a comprehensive understanding of how information systems can aid the realisation of business objectives. With equal and clear coverage of the more technical systems aspects of BIS and the softer, more managerial topics, this book is equally useful to BIS students from Business or Computing backgrounds and for students at an Undergraduate or MBA level.Equipped with a wide variety of long, short and extended case studies from across the UK and Europe as well as examples, review questions and exercises throughout the text, students can easily check their understanding and see how their new-found knowledge applies to real-life business situations.The fifth edition includes: Today's hot topics, such as data warehousing and data mining, knowledge management, ethical issues and responsibility, RAD and extreme programming. A thorough update of coverage of distributed systems, the internet and web support, ERP, UML, and networks and the organisation. Updated references and Case Studies throughout New companion website material including a password protected Instructor's Manual with worked solutions and PowerPoint slides, and free multiple choice questions, web-links and tips for students at www.booksites.net/curtis . "Provides extensive and comprehensive coverage of core IS topics, including development and design"
Keywords: Business,Management information systems,Experts systems ( computer science ),Information storage and retrieval systems; Data processing,Business